EASTERN THINKERS' VIEWS ON PERSONAL PERFORMANCE - Choriyeva Feruza Amrullayevna (European Science Publishing, 2025)
This article is widely covered by the opinions of oriental thinkers about the status of oriental examinations and the Eastern thinkers about the personality.
Keywords: Education, pedagogy, enlightenment, religion, generosity, honesty.